Completeness of Cataract Medical Information Supports the Accuracy of RME Based Diagnosis and Action Codes at RS.X - Heltiani, Nofri; Agusianita; Budiarti, Anggia (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
The completeness of visual acuity (visual acuity) examination results, the completeness of slit lamp examination results, and the accuracy of diagnosis are very important in supporting the accuracy of diagnostic codes and action codes. The initial survey results of 10 e-RMs obtained 6 (60%) accurate and 4 (40%) inaccurate. This is because the results of the visual acuity examination and slit lamp examination are incomplete, resulting in inaccurate diagnostic codes and action codes that impact the quality of data, information, and reports, as well as the accuracy of INA-CBG's rates, which can result in a decrease in the quality of hospital services. This study aims to determine the accuracy of cataract diagnosis and treatment codes based on the completeness of e-RM-based medical information at Hospital X. This type of study is an observational study with a quantitative descriptive design. The study population was 548 e-RMs, with a sample of 85 e-RMs taken by simple random sampling. This study uses secondary data measured by observation sheets, and then the data is processed and analyzed univariately using frequency distribution. The results of this study obtained completeness of visual acuity examination results of 74 (87%), completeness of slit lamp examination results of 77 (91%), accuracy of diagnosis codes of 79 (93%), and accuracy of action codes of 72 (85%). The need to conduct periodic control of the completeness of medical information through medical record audits, establish communication if there is an inaccurate diagnosis, and improve coder skills through coding classification training.